Experimental investigation of temperature effects on zeta potential in microchannels - Xiao, Hui (2014)
Zeta potential is a property of material surface charge when it is surrounded by fluid. The study of Zeta potential has significant meaning in chemical industry since it affects process control, quality control, and product specification. This project presents an investigation on temperature effect on Zeta potential for PDMS microchannels. The Time-interval current-monitoring method is adopted to measure the electro-osmotic flow (EOF) velocity U at evaluated temperature. The Smoluchowski’s equation for EOF velocity is used to predict Zeta potential (ζ). The applied electrical field as well as the solution is selected so that joule heating or electrolysis is negligible. The heat effect of Indium tin oxide (ITO) film is utilized to achieve a temperature range for the microchannel. To enrich the objective, the microchannels surfaces are modified to achieve different solid-liquid contact fraction; consequently the influence of surface hydrophobicity on Zeta potential is investigated. It is found that, when NaCl solution is filled in a PDMS microchannel, the Zeta potential can exhibit a dependence on temperature, the magnitude of Zeta potential increases with temperature. Meanwhile, the PDMS surface with higher solid-liquid contact fraction leads to a higher Zeta potential.